Molecular epidemiology of Clostridioides (Clostridium) difficile strains recovered from clinical trials in the US, Canada and Europe from 2006-2009 to 2012-2015. (October 2018) - Cheknis, Adam; Johnson, Stuart; Chesnel, Laurent; Petrella, Laurica; Sambol, Susan; Dale, Suzanne E.; Nary, Julia; Sears, Pamela; Citron, Diane M.; Goldstein, Ellie J.C.; Gerding, Dale N.
Abstract: The prevalence of C. difficile infection (CDI) and severe CDI are influenced by the prevalence of specific C. difficile strains, which are themselves influenced by antimicrobial susceptibility determinants as well as antimicrobial usage patterns. Restriction endonuclease analysis (REA) typing and antimicrobial susceptibility testing were used to characterize 1808 C. difficile isolates obtained from patients enrolled in four multicenter, multi-country, randomized CDI treatment trials conducted between 2006 and 2009 and between 2012 and 2015. By 2015, the epidemic REA group BI strain (RT027) had decreased in prevalence in North America (US: 43%–18%, Canada: 39%–24%, P < 0.001), but rates of moxifloxacin resistance remained high. In contrast, REA group Y (RT014/020) and DH (RT106) strains, both of which had low rates of moxifloxacin resistance, increased in prevalence (Y strain - US: 6%–17%, Canada: 11%–23%, P < 0.001; DH strain - US: 1%–11%, Canada: 0%–8%, P < 0.0001). In Europe, the BI strain (RT027) was highly prevalent in Eastern European countries in 2015, but was unchanged in other parts of Europe. As in North America, the Y strain (RT014/020) was prevalent in both time periods, but the DH strain was rarely identified. Continued international molecular surveillance of C. difficile will be important to track prevalence of known epidemic strains and detect emergence of new strains of potential epidemiologic significance. Highlights: Epidemiology of C. difficile strains from multinational clinical trials is described. Similar REA group strains were identified in North America and Europe. REA group BI decreased in prevalence in North America between 2006 and 2015. BI was prevalent in Eastern European Countries between 2012 and 2015. An emerging strain, REA group DH, increased in North America between 2006 and 2015.